The Analysis Of Cohesive Devices Used In Scopus-Indexed Journal - Tri Prasetya, Laksana (Jolly Journal of English Education, 2024)
This study aims to investigate the most frequent cohesive devices used in the scopus-indexed journal from Indonesia. This study is a purposive sampling from the abstracts of one volume of the scopus-indexed journal. The writers are from many different countries such as Spain, Ukraine, Indonesia and others. This study uses discourse analysis especially for analyzing the text. These texts would be analyzed by using Halliday and Hasan’s concepts in Suzanne Eggins (2004) for grammatical cohesion and Halliday and Matthiessen (2004) for analyzing the lexical cohesion. This sudy shows that demonstrative reference as the most frequent grammatical cohesive devices used in the abstracts and repetition is as the most occurrance of the lexical cohesion in the text. This study suggests for the people who want to write an article in the scopus indexed journal need to be aware of the cohesive devices used in their abstracts in order to make the text accepted by the journal.